TWO YEARS DESCRIPTIVE STUDY OF MACULAR HOLE PATIENTS OPERATED IN DR. KARIADI GENERAL HOSPITAL, SEMARANG - Partomuan, Andreas Tigor; Wildan, Arief (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesMacular hole (MH) is a vitreomacular interface disorder that could cause visual impairment. Clinicalcharacteristics of MH are important for predicting MH treatment outcomes. This study purpose wasto describe MH patients’ characteristics and postoperative outcomes in Dr. Kariadi Hospital. MethodsA retrospective study held on January 2021–December 2022 utilizing patients’ medical records.Preoperative data: sex, age, symptoms, duration of symptoms, origin, preoperative visual acuity(VA), modified Gass classification stage, macular hole index (MHI), and hole forming factor (HFF)were obtained. Postoperative outcomes data: postoperative VA and anatomical closure were alsocollected. Results20(20 eyes) patients were obtained, with 14(70%) female, 12(60%) aged >60 years old, 13(65%)metamorphopsia, 12(60%) central visual loss, 10(50%) preoperative VA 6/24-6/60, 10(50%) durationof symptoms <3 months, and 16(80%) idiopathic origin. OCT (Ocular Coherence Tomography)findings revealed base diameter mean was 780,7 um(+ SD 312). 13 patients (65%) stage 3 of MH,12(60%) MHI <0,5, 12(60%) HFF > 0,9. All patients underwent MH surgery procedures.Postoperative examination showed 10 patients(50%) with VA 6/6-6/20. 11(100%) with preoperativeVA>6/60, 10(100%) with duration of symptoms <3 months, 8(100%) with MHI > 0,5, and 11(100%)with HFF > 0,9 had improved visual acuity and anatomical closure. It also revealed 17(85%) hadanatomical closure. ConclusionThe most common characteristics found in MH patients were female sex, age >60 years old, anddisorder of idiopathic origin. Preoperative VA, duration of symptoms <3 months before surgery, MHI> 0,5, and HFF > 0,9 were positive prognostic factors for better postoperative functional andanatomical outcomes.